Réponses

  • Utilisateur Brainly
2014-03-05T19:50:58+01:00
3(2x+7)-4=7-5(4-3x)
6x+21-4=7-20+15x
-9x=-30
x=30/9

2x(3x-4)=3x(2x-5)-4

6x²-8x=6x²-15x-4
7x=-4
x=-4/7
2014-03-05T19:52:41+01:00
Salut :)

3(2x + 7) - 4 = 7 - 5(4 - 3x)
3 x 2x + 3 x 7 - 4  = 7 - 5 x 4 - 5 x (-3x)
6x + 21 - 4 = 7 - 20 + 15x
6x + 17 = -13 + 15x
17 = -13 + 15x - 6x
17 = -13 + 9x
17 + 13 = 9x
30 = 9x
x = 30/9
x = 10/3

2x (3x - 4) = 3x (2x - 5) - 4

2x x 3x + 2x x (-4) = 3x x 2x + 3x x (-5) - 4
6x² - 8x = 6x² - 15x - 4
6x² - 8x - 6x² = -15x - 4
-8x = -15x - 4
-8x + 15x = -4
7x = -4
x = -4/7

J'espère t'avoir aidé(e)! :)